2023
DOI: 10.21010/ajtcamv17i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Oleifera Leaf Powder for Type 2 Diabetes: A Pilot Clinical Trial

Abstract: Background: Moringa oleifera Lam. (Moringaceae) leaves are commonly used for diabetes in Mali. This pilot clinical study aimed to evaluate its effect on post-prandial blood glucose in preparation for a larger trial. Methods: Diabetic patients and non-diabetic healthy volunteers (35 each) were asked to fast for 13 hours on three occasions. Blood glucose was measured before and after eating 100g of white bread (at 30, 60, 90, 120, 150 and 180 minutes). On their second and third study visits, they were given 1g a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Another study also showed no side among its participants after the intake of MO leaf powder capsules. 7 The limitations of current study were a short duration and small sample of the study. Therefore, further research work is needed to assess either MO leaf capsule also reduce HBA1c level and diabetes type 2 related complications as well with long term use of it or not.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Another study also showed no side among its participants after the intake of MO leaf powder capsules. 7 The limitations of current study were a short duration and small sample of the study. Therefore, further research work is needed to assess either MO leaf capsule also reduce HBA1c level and diabetes type 2 related complications as well with long term use of it or not.…”
Section: Discussionmentioning
confidence: 87%
“…It is usually present in the western sub-Himalayan regions of India, Pakistan, Bangladesh and Afghanistan, however, nowadays, because of its high demand it has been planted for food and medicine in tropical Asia and sub-Saharan Africa. 7 In several parts of the world, MO has been used in the treatment of different diseases other than diabetes mellitus like diarrhea, infections, hypertension, hyperthyroidism, and cancers. 8,9 In Thailand, it is used as daily food ingredient.…”
Section: Introductionmentioning
confidence: 99%
“…Rich. among others [25,172,193,295] (Table 4). Accordingly, all the tested plants showed the desired clinical effects [25,172,193,295].…”
Section: Studiesmentioning
confidence: 99%
“…among others [25,172,193,295] (Table 4). Accordingly, all the tested plants showed the desired clinical effects [25,172,193,295]. These therapeutic effects justify the use of the plants traditionally to treat DM across different communities in Uganda [17,23].…”
Section: Studiesmentioning
confidence: 99%